Diagnostic value of newborn foot length to predict gestational age - Mutia Farah Fawziah; Bambang Soebagyo; Dwi Hidayah (Indonesian Pediatric Society, 2017)
Background Identification of gestational age, especially within 48 hours of birth, is crucial for newborns, as the earlier preterm status is detected, the earlier the child can receive optimal management. Newborn foot length is an anthropometric measurement which is easy to perform, inexpensive, and potentially efficient for predicting gestational age.Objective To analyze the diagnostic value of newborn foot length in predicting gestational age.Methods This diagnostic study was performed between October 2016 and February 2017 in the High Care Unit of Neonates at Dr. Moewardi General Hospital, Surakarta. A total of 152 newborns were consecutively selected and underwent right foot length measurements before 96 hours of age. The correlation between newborn foot length to classify as full term and gestational age was analyzed with Spearman’s correlation test because of non-normal data distribution. The cut-off point of newborn foot length was calculated by receiver operating characteristic (ROC) curve and diagnostic values of newborn foot length were analyzed by 2 x 2 table with SPSS 21.0 software.Results There were no significant differences between male and female newborns in terms of gestational age, birth weight, choronological age, and newborn foot length (P>0.05). Newborn foot length and gestational age had a significant correlation (r=0.53; P=0.000). The optimal cut-off newborn foot length to predict full term status was 7.1 cm. Newborn foot length below 7.1 cm had sensitivity 75%, specificity 98%, positive predictive value 94.3%, negative predictive value 90.6%, positive likelihood ratio 40.5, negative likelihood ratio 0.25, and post-test probability 94.29%, to predict preterm status in newborns.Conclusion Newborn foot length can be used to predict gestational age, especially for the purpose of differentiating between preterm and full term newborns.